Melanoma/Retinoblastoma Intra-Orbital Lesions (Imaging Results Correlation with Ultrasound and Magnetic Resonance Imaging) - Ahmed, Syed Naseer (Indus Journal of Bioscience Research, 2025)
Objective: This study aims to correlate radiological data on ultrasonography and MRI in order to identify intra-orbital lesions. Methods: In this prospective study, 58 patients were included, representing both sexes. Patients' ages ranged from two to fifty years. All patients referred from the ophthalmology department who were clinically suspected of having orbital or eye abnormalities had CT scans. Radiological data associated with MRI and ultrasound were used to evaluate outcomes among all patients. Full data analysis was carried out using SPSS 24.0. Results: Out of the total number of instances, 49 (84.5%) were determined to be non-traumatic, whereas 9 (15.5%) proved to be traumatic. The most prevalent disease among the 49 cases of non-traumatic lesions was neoplasm, followed by infective and inflammatory lesion cases. Non- traumatic lesions were most commonly retinoblastoma (17 instances, or 34.7% of the total), followed by endocrine orbitopathy and orbital cellulitis. Nine traumatic lesion cases included six fractures (66.7% of the total), two cases of presaptal soft tissue edema (22.2%), and one case of a retained foreign body (orbital or lid) (11.1%). Conclusion: Ct scans help in lesion diagnosis, surgical planning, and monitoring of eye and orbital diseases. MDCT is the gold standard for evaluating bone, detecting calcification, and determining the location, size, and shape of lesions. Orbital and ocular lesions can be evaluated with MDCT.